Is Shallow Convection Sensitive to Environmental Heterogeneities? - Marcin J. Kurowski; Kay Suselj; Wojciech W. Grabowski (Geophysical Research Letters)
Abstract The key assumption underlying convection parameterizations is that rising plumes develop in a horizontally homogeneous environment. With this in mind, we investigate the impact of environmental cloud layer heterogeneities on shallow convection using large‐eddy simulation that applies a driver‐piggybacker methodology. In this approach, two independent sets of thermodynamic variables (primary and secondary) are driven by one dynamics (coupled with the driver) to remove the impact of internal variability of the dynamical system considered. The two thermodynamic sets include either a realistic heterogeneous environment or an environment that is homogenized outside clouds. The key is that homogenization also excludes subsiding shells surrounding cumulus clouds. The results show a small impact of the homogenization on cloud field properties. The physical explanation highlights the role of the subsiding shell shielding a shallow cumulus cloud from its environment.